High-thixotropy conductive silver paste and preparation method thereof
By using composite silver powder and modified sheet silver powder in conductive silver paste, and adding modified polyurea and hydroxyacrylic resin to organic carriers, the problem of insufficient thixotropy of conductive silver paste is solved, and its thixotropy and adhesion is significantly improved. It is suitable for electronic products and solar cells and other fields.
Patent Information
- Application Number
- CN202411636229.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The insufficient thixotropy of conductive silver paste leads to low circuit printing yield and easy fall off of conductive lines, affecting the overall performance of the product.
Compound silver powder and modified sheet silver powder are used as conductive phases, and modified polyurea and hydroxyacrylic resin are added to the organic carrier to improve the thixotropy and adhesion of the silver paste through synergistic effects.
It significantly improves the thixotropy and adhesion of conductive silver paste, improves the yield and comprehensive performance of circuit printing, and is suitable for electronic products and solar cells and other fields.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of conductive silver paste, and in particular to a highly thixotropic conductive silver paste and a preparation method thereof. Background Art
[0002] Conductive silver paste is an electronic functional material that integrates polymer materials, powders, and glass and has rheological properties. It is an important material for hybrid integrated circuits, sensitive components, displays, antennas, electromagnetic shielding, and various electronic discrete devices. It has good application prospects in the fields of solar cells, printed circuit boards, touch screens, sensors, and new energy vehicle manufacturing. Conductive silver paste has excellent electrical conductivity and chemical stability and is widely used in the electronics industry. The conductive properties, low resistance properties, and thixotropy of conductive silver paste have a very important influence on the synthesis of materials and will directly affect the overall performance of the product.
[0003] The thixotropy of conductive silver paste has a great influence on the yield of circuit printing. For example, viscosity, adhesion, leveling, film-forming properties, and solvent volatility will affect the printing performance of the circuit, causing the conductive circuit to fall off the substrate, making the conductive circuit scrapped. Therefore, the thixotropy of conductive silver paste needs to be improved. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a highly thixotropic conductive silver paste and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A highly thixotropic conductive silver paste comprises the following raw materials in percentage by mass: 75-85% composite silver powder, 2-4% glass powder, and 10-25% organic carrier; The composite silver powder is prepared by mixing spherical silver powder and modified flaky silver powder in a mass ratio of 7-9:1-3; Furthermore, the modified flaky silver powder is prepared by the following steps: Step A1, stir the flaky silver powder and 4-mercaptobenzoic acid in anhydrous ethanol for 10 minutes, then ultrasonicate for 30 minutes, place in a 40-60°C water bath to react for 3-7 hours, centrifuge, wash, dry and grind to obtain carboxylated silver powder; Step A2, 2,5-dihydroxyterephthalic acid and nickel nitrate hexahydrate are stirred in a mixture of N,N-dimethylformamide, deionized water and ethanol in a volume ratio of 1:1:1 for 30 minutes, and then 0.4 mol / L sodium hydroxide solution is slowly added and stirred for 20 minutes, and then carboxylated silver powder is added and stirred for 30-50 minutes, and finally transferred to an autoclave, and reacted at 110-130°C for 6-8 hours, centrifuged, washed and dried to obtain modified flaky silver powder; Furthermore, in step A1, the usage ratio of the flaky silver powder, 4-mercaptobenzoic acid and anhydrous ethanol is 10 g: 0.1-0.4 g: 100 mL; Furthermore, in step A2, the dosage ratio of 2,5-dihydroxyterephthalic acid, nickel nitrate hexahydrate, mixed solution, sodium hydroxide solution and carboxylated silver powder is 0.5-1.5 g: 0.6-1.8 g: 150 mL: 10 mL: 1-3 g.
[0006] The organic carrier comprises the following raw materials in percentage by weight: 55-65% pine oil, 25-35% dibutyl phthalate, 1-2% hydroxy acrylic resin, 2-5% modified polyurea, and 2-4% methyl cellulose; The modified polyurea is prepared by the following steps: Step B1, p-phenylenediamine and dimethylacetamide are mixed and stirred evenly, diphenylmethane diisocyanate is added three times within 1 hour, and then the temperature is raised to 65-75° C., and the reaction is stirred for 3-5 hours to obtain a polyurea prepolymer; Step B2, heating the polyurea prepolymer to 80-90° C., adding 2,2-dihydroxymethylpropionic acid and dibutyltin dilaurate, and stirring under nitrogen for 2.5-3.5 hours to obtain a polyurea compound; Step B3, adding dopamine hydrochloride to the above polyurea compound, and heating to 160-180° C. under nitrogen conditions for reflux reaction for 2-6 hours, and then heating to 200° C. for further reaction for 1-2 hours to obtain modified polyurea; Further, in step B1, the dosage ratio of p-phenylenediamine, dimethylacetamide and diphenylmethane diisocyanate is 0.01-0.02 mol: 200 mL: 0.015-0.04 mol; Further, in step B2, the mass ratio of the polyurea prepolymer, 2,2-dimethylolpropionic acid and dibutyltin dilaurate is 3-8:0.5-2:0.0001-0.0002; Furthermore, the mass ratio of dopamine hydrochloride in step B3 to 2,2-dihydroxymethylpropionic acid in step B2 is 0.7-2.83:0.5-2.
[0007] A method for preparing a highly thixotropic conductive silver paste comprises the following steps: Step S1, weighing raw materials according to mass percentage, adding pine oil, dibutyl phthalate, hydroxy acrylic resin and methyl cellulose into a mixer, stirring for 1-2 hours at 30-40° C. and 200-400 rpm / min, then adding modified polyurea and continuing stirring for 40-60 minutes to obtain an organic carrier; Step S2, weighing the raw materials according to the mass percentage, mixing the glass powder and the composite silver powder in a blender, and then adding the organic carrier and mixing and stirring for 10-30 minutes, and then pouring the obtained slurry into a three-roll grinder and grinding it to a fineness of 7-10 μm to obtain a highly thixotropic conductive silver paste.
[0008] Beneficial effects of the present invention: The conductive silver paste prepared by the present invention is prepared by using spherical silver powder and modified flaky silver powder as conductive phases, glass powder as non-bonding phase, and adding an organic carrier for mixing and stirring; the modified flaky silver powder has better conductivity than the flaky silver powder, and has better dispersibility and stability in the matrix; modified polyurea and hydroxy acrylic resin are introduced into the organic carrier, and the synergistic effect between them is utilized to improve the thixotropy and adhesion of the silver paste. Therefore, the conductive silver paste of the present invention has good application prospects in the fields of electronic products, solar cells, etc.
[0009] In the modified flaky silver powder, carboxylated silver powder is first obtained by the reaction between the mercapto group in 4-mercaptobenzoic acid and silver powder; then the carboxyl group on the surface of the carboxylated silver powder is used to participate in the synthesis of Ni-MOF (Ni-MOF is a nickel-based metal organic framework) to obtain modified flaky silver powder. The modified flaky silver powder and spherical silver powder work synergistically as the conductor in the conductive silver paste, providing the silver paste with excellent conductive properties; wherein, the modified flaky silver powder is synthesized in situ, and MOF is coated on the surface of the flaky silver powder. The MOF coating layer can form a protective film on the surface of the silver powder to prevent agglomeration and precipitation between the silver powder particles, thereby ensuring that the silver powder can be evenly dispersed in the conductive silver paste, significantly improving the dispersibility and stability of the silver powder; after the conductive silver paste is sintered, a continuous conductive network is formed between the silver powder particles, and the MOF coating layer helps to reduce the pores in the film layer after sintering, increase the conductive path between the silver powder, thereby reducing the square resistance of the film layer and improving the comprehensive performance of the silver paste. In addition, the nickel element contained in the MOF layer can also reduce the sintering temperature of the conductive silver paste, allowing the conductive paste to be cured at a lower temperature, which is suitable for application scenarios that require low-temperature curing.
[0010] In the modified polyurea, the -NH2 group in p-phenylenediamine and the -NCO group in diphenylmethane diisocyanate are first reacted to obtain a polyurea prepolymer; then, in the presence of a catalyst, the terminal isocyanate group in the polyurea prepolymer and the hydroxyl group in 2,2-dihydroxymethylpropionic acid are reacted to obtain a polyurea compound; finally, the amino group in dopamine hydrochloride and the carboxyl group in the polyurea compound are reacted to obtain a modified polyurea. The addition of modified polyurea can synergize with hydroxy acrylic resin to improve the thixotropy of silver paste. This is because the modified polyurea contains a large number of polar groups, such as urea, amide, hydroxyl and carbamate groups. Their presence can produce strong hydrogen bonds between the molecules of the modified polyurea, and hydrogen bonds can form a network structure in the matrix. This structure is destroyed under the action of shear force, resulting in a decrease in the viscosity of the paste. After the shear force is removed, the hydrogen bonds are re-formed, and the viscosity of the paste is restored, thereby giving the matrix good thixotropic properties. The carbamate groups contained in the modified polyurea also show good moisture resistance, which improves the moisture resistance of the modified polyurea and effectively reduces the decrease in adhesion of the polyurea due to poor moisture resistance. In addition, the catechol structure contained in the modified polyurea also improves the adhesion of the conductive silver paste, so that the conductive silver paste has excellent adhesion after printing. DETAILED DESCRIPTION
[0011] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0012] Example 1: The modified flaky silver powder is prepared by the following steps: Step A1, stirring 10 g of flaky silver powder and 0.1 g of 4-mercaptobenzoic acid in 100 mL of anhydrous ethanol for 10 min, then ultrasonically treating for 30 min, placing in a 40° C. water bath to react for 3 h, centrifuging, washing, drying, and grinding to obtain carboxylated silver powder; Step A2, 0.5 g of 2,5-dihydroxyterephthalic acid and 0.6 g of nickel nitrate hexahydrate were stirred in 150 mL of a mixture of N,N-dimethylformamide, deionized water and ethanol in a volume ratio of 1:1:1 for 30 min, and then 10 mL of 0.4 mol / L sodium hydroxide solution was slowly added and stirred for 20 min, and then 1 g of carboxylated silver powder was added and stirred for 30 min, and finally transferred to an autoclave, and reacted at 110° C. for 6 h, centrifuged, washed and dried to obtain modified flaky silver powder.
[0013] The modified polyurea is prepared by the following steps: Step B1, 0.01 mol of p-phenylenediamine and 200 mL of dimethylacetamide were mixed and stirred evenly, 0.015 mol of diphenylmethane diisocyanate was added three times within 1 hour, and then the temperature was raised to 65° C. and stirred for reaction for 3 hours to obtain a polyurea prepolymer; Step B2, heating the above 3 g of polyurea prepolymer to 80° C., adding 0.5 g of 2,2-dimethylolpropionic acid and 0.0001 g of dibutyltin dilaurate, stirring and reacting under nitrogen for 2.5 h to obtain a polyurea compound; Step B3, add 0.7 g of dopamine hydrochloride to the above polyurea compound, and heat to 160° C. under nitrogen for reflux reaction for 2 h, and then heat to 200° C. for further reaction for 1 h to obtain modified polyurea.
[0014] Example 2: The modified flaky silver powder is prepared by the following steps: Step A1, stirring 10 g of flaky silver powder and 0.25 g of 4-mercaptobenzoic acid in 100 mL of anhydrous ethanol for 10 min, then ultrasonically treating for 30 min, placing in a 50° C. water bath to react for 5 h, centrifuging, washing, drying, and grinding to obtain carboxylated silver powder; Step A2, 1 g of 2,5-dihydroxyterephthalic acid and 1.2 g of nickel nitrate hexahydrate were stirred in 150 mL of a mixture of N,N-dimethylformamide, deionized water and ethanol in a volume ratio of 1:1:1 for 30 min, and then 10 mL of 0.4 mol / L sodium hydroxide solution was slowly added and stirred for 20 min, and then 2 g of carboxylated silver powder was added and stirred for 40 min, and finally transferred to an autoclave, and reacted at 120° C. for 7 h, centrifuged, washed and dried to obtain modified flaky silver powder.
[0015] The modified polyurea is prepared by the following steps: Step B1, 0.015 mol of p-phenylenediamine and 200 mL of dimethylacetamide were mixed and stirred evenly, 0.025 mol of diphenylmethane diisocyanate was added three times within 1 hour, and then the temperature was raised to 70° C. and stirred for reaction for 4 hours to obtain a polyurea prepolymer; Step B2, heating the above 5 g polyurea prepolymer to 85° C., adding 1 g 2,2-dihydroxymethylpropionic acid and 0.00015 g dibutyltin dilaurate, stirring and reacting for 3 h under nitrogen conditions to obtain a polyurea compound; Step B3, add 1.5 g of dopamine hydrochloride to the above polyurea compound, and heat to 170° C. under nitrogen for reflux reaction for 4 h, and then heat to 200° C. for further reaction for 1.5 h to obtain modified polyurea.
[0016] Example 3: The modified flaky silver powder is prepared by the following steps: Step A1, stirring 10 g of flaky silver powder and 0.4 g of 4-mercaptobenzoic acid in 100 mL of anhydrous ethanol for 10 min, then ultrasonically treating for 30 min, placing in a 60° C. water bath for reaction for 7 h, centrifuging, washing, drying, and grinding to obtain carboxylated silver powder; Step A2, 1.5 g of 2,5-dihydroxyterephthalic acid and 1.8 g of nickel nitrate hexahydrate were stirred in 150 mL of a mixture of N,N-dimethylformamide, deionized water and ethanol in a volume ratio of 1:1:1 for 30 min, and then 10 mL of 0.4 mol / L sodium hydroxide solution was slowly added and stirred for 20 min, and then 3 g of carboxylated silver powder was added and stirred for 50 min, and finally transferred to an autoclave, and reacted at 130° C. for 8 h, centrifuged, washed and dried to obtain modified flaky silver powder.
[0017] The modified polyurea is prepared by the following steps: Step B1, 0.02 mol of p-phenylenediamine and 200 mL of dimethylacetamide were mixed and stirred evenly, 0.04 mol of diphenylmethane diisocyanate was added three times within 1 hour, and then the temperature was raised to 75° C. and stirred for reaction for 5 hours to obtain a polyurea prepolymer; Step B2, heating the above 8 g of polyurea prepolymer to 90° C., adding 2 g of 2,2-dihydroxymethylpropionic acid and 0.0002 g of dibutyltin dilaurate, stirring and reacting under nitrogen for 3.5 h to obtain a polyurea compound; Step B3, add 2.83 g of dopamine hydrochloride to the above polyurea compound, and heat to 180° C. under nitrogen for reflux reaction for 6 h, and then heat to 200° C. for further reaction for 2 h to obtain modified polyurea.
[0018] Example 4: A method for preparing a highly thixotropic conductive silver paste comprises the following steps: Step S1, weighing raw materials according to mass percentage, adding 65% pine oil, 25% dibutyl phthalate, 1% hydroxy acrylic resin and 2% methyl cellulose into a mixer, stirring for 1 hour at 30° C. and 200 rpm / min, then adding 2% modified polyurea prepared in Example 1 and continuing stirring for 40 minutes to obtain an organic carrier; Step S2, mixing the spherical silver powder and the modified flaky silver powder prepared in Example 1 in a mass ratio of 7:3 to obtain a composite silver powder; weighing the raw materials according to mass percentage, mixing 2% of the glass powder and 75% of the composite silver powder in a blender, and then adding 23% of the organic carrier and mixing and stirring for 10 minutes, and then pouring the obtained slurry into a three-roll grinder and grinding it to a fineness of 7 μm to obtain a highly thixotropic conductive silver paste.
[0019] Example 5: A method for preparing a highly thixotropic conductive silver paste comprises the following steps: Step S1, weighing raw materials according to mass percentage, adding 60% pine oil, 32% dibutyl phthalate, 1.5% hydroxy acrylic resin and 3% methyl cellulose into a blender, stirring for 1.5 hours at 35° C. and 300 rpm / min, then adding 3.5% of the modified polyurea prepared in Example 2 and continuing stirring for 50 minutes to obtain an organic carrier; Step S2, mixing the spherical silver powder and the modified flaky silver powder prepared in Example 2 in a mass ratio of 8:2 to obtain a composite silver powder; weighing the raw materials according to mass percentage, mixing 3% of the glass powder and 80% of the composite silver powder in a blender, and then adding 17% of the organic carrier and mixing and stirring for 20 minutes, and then pouring the obtained slurry into a three-roll grinder and grinding it to a fineness of 8 μm to obtain a highly thixotropic conductive silver paste.
[0020] Example 6: A method for preparing a highly thixotropic conductive silver paste comprises the following steps: Step S1, weighing raw materials according to mass percentage, adding 59% pine oil, 30% dibutyl phthalate, 2% hydroxy acrylic resin and 4% methyl cellulose into a blender, stirring for 2 hours at 40° C. and 400 rpm / min, then adding 5% of the modified polyurea prepared in Example 3 and continuing stirring for 60 minutes to obtain an organic carrier; Step S2, mixing the spherical silver powder and the modified flaky silver powder prepared in Example 3 in a mass ratio of 9:1 to obtain a composite silver powder; weighing the raw materials according to mass percentage, mixing 4% of the glass powder and 85% of the composite silver powder in a blender, and then adding 11% of the organic carrier and mixing and stirring for 30 minutes, and then pouring the obtained slurry into a three-roll grinder and grinding it to a fineness of 10 μm to obtain a highly thixotropic conductive silver paste.
[0021] Comparative Example 1: This comparative example is a conductive silver paste. The difference from Example 5 is that flaky silver powder is used instead of the modified flaky silver powder prepared in Example 2, and the rest is the same.
[0022] Comparative Example 2: This comparative example is a conductive silver paste. The difference from Example 5 is that commercially available polyurea is used instead of the modified polyurea prepared in Example 2, and the rest is the same.
[0023] Performance test: The conductive silver pastes prepared in Examples 4-6 and Comparative Examples 1-2 were subjected to performance tests: Thixotropy: The viscosity was measured at rotor speeds of 5 r / min and 50 r / min using a BROOKFIELD rotary viscometer (rotor No. 14), and the thixotropic index It was calculated according to the following formula: It = η5 / η50, where It is the thixotropic index; η5 is the viscosity measured at a rotor speed of 5 r / min; η50 is the viscosity measured at a rotor speed of 50 r / min; Square resistance: The conductive silver paste prepared in Examples 4-6 and Comparative Examples 1-2 is used to print fine conductive circuits on the ITO / PET film of a semi-automatic screen printer using an 800-mesh polyester screen. The fine conductive circuits printed by the screen printing are five serpentine lines, and the line width / line spacing is 50μm / 50μm, 60μm / 60μm, 70μm / 70μm, 80μm / 80μm, 100μm / 100μm, respectively, and the thickness is 2μm to 6μm; after baking at 130°C for 60 minutes, observe under a microscope that the surface of the conductive circuit with a line width / line spacing of 50μm and above is flat, and the edges are clear and smooth. Then use a digital multimeter to test the resistance value of the printed conductor, and then calculate the square resistance; Adhesion: Adopt the 100-grid test (ITO / PT film) specified in the national standard, 3M 600 tape, vertical pull, ASTM standard; the above test results are shown in Table 1: Table 1: Performance test results
[0024] As can be seen from Table 1, after the thixotropy, square resistance and adhesion tests, the conductive silver paste prepared by the present invention has a thixotropy index of 5.76-5.91, a square resistance of 26mΩ / ¨ / 10μm-29mΩ / ¨ / 10μm, and a uniform adhesion grade of 5B, indicating that the conductive silver paste has excellent conductivity and adhesion as well as high thixotropy.
[0025] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A highly thixotropic conductive silver paste, characterized in that: The raw materials include the following mass percentages: 75-85% composite silver powder, 2-4% glass powder, and 10-25% organic carrier; The composite silver powder is prepared by mixing spherical silver powder and modified flaky silver powder in a mass ratio of 7-9:1-3; The modified flaky silver powder is prepared by the following steps: Step A1, stir the flaky silver powder and 4-mercaptobenzoic acid in anhydrous ethanol for 10 minutes, then ultrasonicate for 30 minutes, place in a 40-60°C water bath to react for 3-7 hours, centrifuge, wash, dry and grind to obtain carboxylated silver powder; Step A2, 2,5-dihydroxyterephthalic acid and nickel nitrate hexahydrate are stirred in a mixture of N,N-dimethylformamide, deionized water and ethanol in a volume ratio of 1:1:1 for 30 minutes, and then 0.4 mol / L sodium hydroxide solution is slowly added and stirred for 20 minutes, and then carboxylated silver powder is added and stirred for 30-50 minutes, and finally transferred to an autoclave, and reacted at 110-130°C for 6-8 hours, centrifuged, washed and dried to obtain modified flaky silver powder.
2. A highly thixotropic conductive silver paste according to claim 1, characterized in that: In step A1, the usage ratio of flaky silver powder, 4-mercaptobenzoic acid and anhydrous ethanol is 10 g: 0.1-0.4 g: 100 mL.
3. The highly thixotropic conductive silver paste according to claim 1, characterized in that: In step A2, the usage ratio of 2,5-dihydroxyterephthalic acid, nickel nitrate hexahydrate, mixed solution, sodium hydroxide solution and carboxylated silver powder is 0.5-1.5 g: 0.6-1.8 g: 150 mL: 10 mL: 1-3 g.
4. The highly thixotropic conductive silver paste according to claim 1, characterized in that: The organic carrier comprises the following raw materials in percentage by mass: 55-65% pine oil, 25-35% dibutyl phthalate, 1-2% hydroxy acrylic resin, 2-5% modified polyurea, and 2-4% methyl cellulose.
5. The highly thixotropic conductive silver paste according to claim 1, characterized in that: The modified polyurea is prepared by the following steps: Step B1, p-phenylenediamine and dimethylacetamide are mixed and stirred evenly, diphenylmethane diisocyanate is added three times within 1 hour, and then the temperature is raised to 65-75° C., and the reaction is stirred for 3-5 hours to obtain a polyurea prepolymer; Step B2, heating the polyurea prepolymer to 80-90° C., adding 2,2-dihydroxymethylpropionic acid and dibutyltin dilaurate, and stirring under nitrogen for 2.5-3.5 hours to obtain a polyurea compound; Step B3, add dopamine hydrochloride to the above polyurea compound, and under nitrogen conditions, heat to 160-180° C. for reflux reaction for 2-6 hours, and then heat to 200° C. for further reaction for 1-2 hours to obtain modified polyurea.
6. The highly thixotropic conductive silver paste according to claim 1, characterized in that: In step B1, the usage ratio of p-phenylenediamine, dimethylacetamide and diphenylmethane diisocyanate is 0.01-0.02 mol: 200 mL: 0.015-0.04 mol.
7. The highly thixotropic conductive silver paste according to claim 1, characterized in that: In step B2, the mass ratio of the polyurea prepolymer, 2,2-dihydroxymethylpropionic acid and dibutyltin dilaurate is 3-8:0.5-2:0.0001-0.0002.
8. The highly thixotropic conductive silver paste according to claim 1, characterized in that: The mass of dopamine hydrochloride in step B3 and 2,2-dihydroxymethylpropionic acid in step B2 is 0.7-2.83:0.5-2.
9. A method for preparing the highly thixotropic conductive silver paste according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step S1, weighing raw materials according to mass percentage, adding pine oil, dibutyl phthalate, hydroxy acrylic resin and methyl cellulose into a mixer, stirring for 1-2 hours at 30-40° C. and 200-400 rpm / min, then adding modified polyurea and continuing stirring for 40-60 minutes to obtain an organic carrier; Step S2, weighing the raw materials according to the mass percentage, mixing the glass powder and the composite silver powder in a blender, and then adding the organic carrier and mixing and stirring for 10-30 minutes, and then pouring the obtained slurry into a three-roll grinder and grinding it to a fineness of 7-10 μm to obtain a highly thixotropic conductive silver paste.
Citation Information
Patent Citations
Conductive paste, and conductive coating film and conductive film using the same
CN101523510A
Metal particle dispersion, article and sintered film using metal particle dispersion, and method for producing sintered film
CN104822767A
Printed electrode material, preparation method of printed electrode and application of printed electrode in quinolone pesticide detection
CN112697866A
Conductive silver paste containing supported Ag-MOF and preparation method thereof
CN115512872A
High-thixotropy conductive silver paste and preparation method thereof
CN118430894A
Cited By
Low-silver-content composite conductive silver paste based on three-dimensional conductive network and preparation method
CN120690485A